A GLOBAL PERSPECTIVE A KEYWORD FOR DESIGN EDUCATION FACING XXI CENTURY - H Istanto, Freddy (Nirmana, 2002)
Globalization has brought a great effect to human life either economically%2C politically%2C socially or culturally. The free market and the development of information and communication technology have made the job competition become strict. This effect has also influenced the education field especially for the design education. In facing the challenge of the 21st century%2C the design education should make some restructuring as anticipation. This paper will explain about the importance of the education that implants the global perspective view towards the student. Substantial and Perceptual dimension brings some challenge that force the educators to prepare more innovative and new approaches for their teaching method. The studio learning method that surely brings benefit to the student-centered learning will become the focus of the design education. Thus%2C besides stressing on the importance of the academic subject that can shape the student s attitude and competency in facing the 21st century s challenge%2C Petra Christian University also does some trials towards the problem-based learning and case-based learning system for its studio teaching and learning process. Abstract in Bahasa Indonesia : Globalisasi membawa dampak yang sangat besar bagi kehidupan manusia. Globalisasi tidak hanya berdampak pada masalah ekonomi saja%2C tetapi juga bagi berpengaruh pada dimensi politik%2C sosial adan budaya. Globalisasi juga membawa ekonomi pada sistim pasar bebas dunia%2C demikian juga kemajuan teknologi komunikasi dan sistim informasi membawa persaingan pasar dan lapangan kerja yang sangat ketat dimana-mana. Kondisi ini juga berdampak pada dimensi pendidikan%2C demikian juga halnya pada pendidikan desain. Menyongsong abad 21 pendidikan desain juga harus mulai mengadakan restrukturisasi untuk mengantisipasinya. Tulisan ini akan mengulas pentingnya pendidikan yang menanamkan kepada peserta didik%2C pentingnya perspektif global dalam menghadapi globalisasi ini. Dimensi substansial dan dimensi perseptual sebagai unsur perspektif global membawa tantangan tersendiri bagi para pendidik untuk menyiapkan sistim pendidikan yang lebih inovatif dan memerlukan pendekatan-pendekatan baru dalam proses belajar-mengajarnya. Model pembelajaran dengan sistim studio diyakini sesuai untuk pendidikan desain di era global yang berdasar pada student-centered-learning. Model ini dijalankan oleh Universitas Kristen Petra dengan metoda Problem Based learning dan Case based learning pada sistim studionya disamping tetap memberikan penekanan pada kompetensi dan pembentukan sikap menghadapi abad XXI. globalization%2C global perspective%2C design education%2C design education in 21 century.